Gabe Halak Batak; Batak Toba Ethnic Bodiedness Traditions as a Reference for Actor Training - Ilham Rifandi; Ifwanul Hakim; Nazlah Syahaf Nasution (Universitas Negeri Medan, 2023)
Gabe Halak Batak is a term that was born from research on the bodiedness traditions of the Batak Toba people which means